2013
DOI: 10.1603/ec13331
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Cranberries to <I>Drosophila suzukii</I> (Diptera: Drosophilidae)

Abstract: Drosophila suzukii Matsumura (Diptera: Drosophilidae), commonly referred to as the spotted wing drosophila, is an exotic species that has proven a troublesome pest of fruit production in the United States. The fly targets small fruit and thus represents a concern for the U.S. cranberry industry. Two studies were conducted to assess whether cranberries may serve as hosts for D. suzukii. In the first study, the suitability of ripe, unripe, and over-ripe cranberries were assayed by examining adult oviposition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 6 publications
1
30
0
Order By: Relevance
“…The quantitative differences in volatiles measured in our experiments should not have played a role due to the no-choice experimental design. In contrast to cranberries, where SWD can only develop within wounded decaying fruit (Steffan et al 2013), this study showed for the first time that SWD can develop from egg to adult stage in both unwounded and wounded mistletoe berries. Furthermore, we showed that adult female SWD were able to subsist on unwounded and wounded berries of mistletoes for at least eight days.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The quantitative differences in volatiles measured in our experiments should not have played a role due to the no-choice experimental design. In contrast to cranberries, where SWD can only develop within wounded decaying fruit (Steffan et al 2013), this study showed for the first time that SWD can develop from egg to adult stage in both unwounded and wounded mistletoe berries. Furthermore, we showed that adult female SWD were able to subsist on unwounded and wounded berries of mistletoes for at least eight days.…”
Section: Discussionmentioning
confidence: 58%
“…SWD laid more eggs in artificially wounded berries compared with undamaged berries. This effect is also known from other fruit crops, e.g., cranberries and grapes (Steffan et al 2013;Ioriatti et al 2015). This was more likely due to easier access to the fruit pulp in wounded fruits than to the emitted volatiles, because we could not detect qualitative differences between intact and damaged fruits.…”
Section: Discussionmentioning
confidence: 71%
“…Hamby et al (2012) indicate that an association exists between spotted wing drosophila and certain yeast species and that these yeasts may attract spotted wing drosophila females for oviposition and feeding. Apart from chemical stimulus and requirements, physical characteristics of suitable host fruits might also facilitate oviposition, as was shown by Steffan et al (2013) with D. suzukii oviposition into wounded or unwounded cranberries. Many fruit species may be physiologically suitable hosts for D. suzukii growth and development, but are less likely infested by the ßy simply because the adult ßy is unable to successfully lay eggs in the fruit ßesh (hereafter referred to oviposition success) owing to the fruit surface characteristics such as a relatively hard (Þrm) or thick surface skin.…”
Section: Abstract Stone Fruit Peach Fuzz Indumenta Drosophila Suzmentioning
confidence: 99%
“…Hawaiian Islands are not represented although SWD presence has been known since 1980 (Hauser 2011 and references herein). The information provided is based on a compilation of reports from plant protection services and extension specialists, and on published scientific articles Burrack et al 2013), while some other small fruits, such as cranberries, are unsuitable unless damaged (Steffan et al 2013). Certain fruits (e.g., apples, pears, tomatoes) can also be infested if split or previously damaged (Lee et al 2011a), but SWD is not a significant pest of these crops.…”
Section: Life History Damage and Host Rangementioning
confidence: 99%